STUDY ON THE USE OF SPACE FOR THE RESIDENTIAL LAND SYSTEM IN THE SPATIAL PLAN OF THE AREA OF BATANG KUIS DISTRICT, DELI SERDANG REGENCY - Dimas Setiawan; Wahyu Hidayat (Yayasan Sinergi Multidimensi Kreatif, 2025)
The form of space utilization as residential land is a form of expression of human activities that use space as a place to live. This study aims to determine the level of suitability of space use and to determine the use of space for the residential land system in the Regional Spatial Plan (RTRW) in the Batang Kuis sub-district area. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques are in the form of observation, interviews and documentation. The results of the study show that the level of suitability of space utilization in general is quite good, with around 90% of the area having complied with the stipulated provisions. The Regional Spatial Plan (RTRW) policy has been an effective guide for developers in planning the development of residential areas. The use of space for the residential land system in the Regional Spatial Plan in the Batang Kuis District area shows the importance of the Regional Spatial Plan policy in directing the development of the area in a planned and sustainable manner. Of the total area of 40.34 km², most of the land, which is 38.14 km², has been appropriately used as a residential area. However, there are still 2.20 km² of land that is converted without its designation, often in the form of productive land such as rice fields and fields.